Analisis fenomena bahasa pada gen z di era digital - ridwan, muhammad zainur (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze linguistic phenomena among Generation Z in the digital age, particularly in the context of language politeness on social media. Rapid advancements in information technology have transformed societal communication patterns, with social media becoming the primary means of interaction, especially for Generation Z, who have grown up alongside digital technology. This situation has given rise to a tendency toward the use of language that is shorter, more expressive, and less formal—known as slang. The method used in this study is a descriptive qualitative approach, examining linguistic phenomena occurring across various social media platforms. The results indicate that Generation Z prefers slang because it is considered practical and aligned with the nature of digital communication. However, the use of such language often disregards principles of linguistic politeness, such as appropriate word choice, clear sentence structure, and communication context. This phenomenon has the potential to cause misunderstandings and lower the quality of communication. On the other hand, social media also has a positive impact as a medium for creativity and learning when used wisely. Therefore, educational efforts are needed to raise Generation Z’s awareness of using proper and polite language, both in online and offline communication.